ENGAGING A DIVERSE PATIENT AND CARE PARTNER COUNCIL TO REFINE DEMENTIA CARE DIGITAL HEALTH TOOLS. (20th December 2022) - Cassidy, Jessica; Fisher, Mary; Romeo, Evelyn; Holden, Samantha; Caffrey, Melanie; Nease, Donald; Lum, Hillary
Abstract: Digital health tools have potential to reduce health disparities for persons with dementia and their family care partners (i.e., dementia dyads). We aimed to promote digital health equity through engaging stakeholders to identify priorities and suggestions for refinements to digital health tools. We convened a council, "Memory Research Partners in Caring and Technology" comprised of three dementia dyads, two care partners, and 10 community members with experience as research partners. The council met six times over seven months. Methods of engagement included: a) delivering preparatory educational materials and hosting guest speakers; b) World Café participatory methods and small group discussions using Google jamboards; and c) individual consultations with partners for additional input. Data was analyzed using rapid qualitative analysis and member checking with research partners. We evaluated engagement methods with a research partner survey and analyzed responses using descriptive statistics. Research partners identified key priorities for equitable refinement of digital health tools, including: 1) Communicating with dementia dyads based on their preferences; 2) Creating user-friendly patient portals; 3) Ensuring digital health tools offer dementia dyads convenience; 4) Providing technology supports; and 5) Facilitating connection to community resources. Stakeholder feedback regarding project engagement indicated majority strongly agreed their input was accurately heard (69%); communication and scheduling was accommodating (77%); they contributed to the research project (69%); and they gained new knowledge on digital tools (54%) and dementia (85%). Research partner insights and ongoing member checking will inform future next steps towards improving dementia care coordination and communication using digital tools.